Answers

The Brainliest Answer!
2016-02-08T21:14:29+05:30
Let the digits be x and y
Then actual number = 10x+y
Sum of digits = x+y = 9   ----------------(1)
27 added to the number = 10x+y+27
Then the number is reversed
⇒ 10x+y+27 = 10y+x
⇒ 10x+y+27-10y-x =0
⇒ 9x - 9y +27 = 0
⇒ 9(x - y +3) = 0
⇒ x - y +3 = 0/9
⇒ x - y +3 =0
⇒ x - y = -3    ----------------------(2)
Solving (1) and (2)
x + y = 9
x - y = -3

⇒ 2x = 6
⇒ x =6/2
∴ x = 3
Substituting x =3 in eq (1)
⇒ x + y = 9
⇒ 3 + y =9
⇒ y = 9 -3
∴ y = 6
The number = 10x+y
= 10(3) + 6
= 30+6
= 36
2 4 2